The interaction between excavation of Trojane tunnel and an anchored pile retaining wall - J. Likar; V. Jovicic (The Southern African Institute of Mining and Metallurgy, 2003)
The knowledge of the geological sequence and hydrological conditions in the area of portals was the basis for the design of the entry of the highway into tunnel Trojane. Mudstone, claystone and sandstone dominate the rock layering, which is tectonically reworked and contains structural anomalies. The complexity of the sequence makes it impossible to survey all the relevant features along the full 3km length of the tunnel. Sudden and frequent transitions between litological sequences impose potential instabilities and make the excavation of the tunnel particularly difficult. The initial survey established the zones of potential failures. These were monitored using topographic survey and inclinometers with an aim to make further geotechnical analyses more reliable and adjusted to the ground conditions. The analyses of the wall construction and the results of the monitoring showed that the design of the retaining wall was adequate. La connaissance de la séquence géologique et des conditions hydrologiques dans l'aire des portails a été la base pour la planification de l'entrée de l'autoroute dans le tunnel Trojane. Le schiste, l'argilite et le grès dominent la couche rocheuse qui est tectoniquement transformée et contient les anomalies structurales. A cause de la complexité de la séquence, il est impossible de revoir toutes les particularités le long des 3 kilomètres de la toute longueur du tunnel. Les transitions soudaines et fréquentes entre les séquences lithologiques imposent l'instabilité potentielle et font l'excavation du tunnel particulièrement difficile. La revue initiale a été établie sur les zones où il existe l'éboulement potential. Elles étaient contrôlées à l'aide de la revue topographique et de l'inclinomètre pour que les analyses géotechniques suivantes soient plus sûres et adaptées aux conditions du sol. Les analyses de la construction des murs et des résultats du contrôle ont montré que la planification du mur réteneur était correspondante. Der Autobahneingang in den Trojane Tunnel war projektiert auf Basis von der Kenntnis der geologischen und hydrogeologischen Bedingungen in dem Portalgebiet. Das Gebiet besteht aus dem Tonstein und dem Sandstein. Die Schichten sind tektonisch verformt und sind deswegen sehr heterogen. Die anfaenglichen Untersuchungen haben die Zonen von den potentiellen Bruechen definiert. Weitere geotechnische Analysen waren fitted an reale geologische Bedingungen durch das Monitoring der potentiellen Bruchzonen, welches aus den topographyschen Messungen und Inklinometerdaten entstand. Die Analyse des Wandbaues und die Resultate von dem Monitoring haben erwiesen, dass die Wandprojektierung entsprechend war.